UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN SCRAPBOOK PADA MATERI PENDIDIKAN PANCASILA KELAS III SD NEGERI LAMKUNYET ACEH BESAR - Wulan Purnama Wulan; Mislinawati; Nurmasyitah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to determine teacher activities, student activities, and improvement of learning outcomes of third-grade students at SD Negeri Lamkunyet Aceh Besar through the use of scrapbook learning media on Pancasila Education material. This research used a qualitative approach with Classroom Action Research (CAR) type conducted in two cycles, where each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were the third-grade teacher and 20 third-grade students at SD Negeri Lamkunyet Aceh Besar. Data collection techniques were conducted through observation and tests (pretest-posttest). Data analysis of teacher and student activities used percentage formulas, while analysis of learning outcomes used average score calculations and classical completeness percentages. The research results showed that teacher activities increased from 66% (Good category) in cycle I to 81% (Very Good category) in cycle II. Student activities also increased from 65.79% (Fair category) in cycle I to 75% (Good category) in cycle II. Student learning outcomes showed significant improvement, with average scores increasing from 48 in the pre-action stage to 65 in cycle I, and reaching 74.5 in cycle II. Classical completeness increased from 10% before the action to 60% in cycle I, and reached 85% in cycle II, exceeding the minimum target of 80%. Thus, it can be concluded that the use of scrapbook learning media proved effective in improving teacher activities, student activities, and student learning outcomes on Pancasila Education material for third-grade students at SD Negeri Lamkunyet Aceh Besar. Scrapbook media was able to create active, creative, engaging, and meaningful learning for students